Registration of 'Goldenhart', a Two‐Rowed Spring Food Barley. Issue 2 (25th April 2019) - Hu, G.; Evans, C. P.; Satterfield, K.; Ellberg, S.; Marshall, J. M.; Schroeder, K.; Obert, D. E.
Abstract : 'Goldenhart' (Reg. No. CV‐368, PI 688445) is a two‐rowed spring hull‐less food barley ( Hordeum vulgare L.) developed by the USDA‐ARS, Aberdeen, ID, in cooperation with the University of Idaho Agricultural Experiment Station, and released in 2017. Goldenhart is derived from the cross of 02HR 4590/'CDC Fibar' and was advanced through modified bulk pedigree F1 – F5 . Goldenhart was tested at the USDA‐ARS, and all other cooperative trials, as line 2Ab09‐X06F058HL‐31. Goldenhart was tested over 40 location years and has shown better yield under irrigated conditions than 'CDC Alamo' and 'Transit' and better yield in dryland areas than all the current two‐rowed spring hull‐less food barley cultivars, 'Julie', Transit, and CDC Alamo. Moreover, Goldenhart has shown significantly higher yields than Transit, the barley check with similar β‐glucan concentration, in both irrigated and dryland conditions. Goldenhart will be a good hull‐less cultivar and a better alternative than Transit in the food barley production market.